Materialism across the life span An age-period-cohort analysis. [article]. - Jaspers, E. D.
This research examined the development of materialism across the life span. Two initial studies revealed that (a) lay beliefs were that materialism declines with age and (b) previous research findings also implied a modest, negative relationship between age and materialism. Yet, previous research has considered age only as a linear control variable, thereby precluding the possibility of more intricate relationships between age and materialism. Moreover, prior studies have relied on cross-sectional data and thus confound age and cohort effects. To improve on this, the main study used longitudinal data from 8 waves spanning 9 years of over 4,200 individuals (16 to 90 years) to examine age effects on materialism while controlling for cohort and period effects. Using a multivariate multilevel latent growth model, it found that materialism followed a curvilinear trajectory across the life span, with the lowest levels at middle age and higher levels before and after that. Thus, in contrast to lay beliefs, materialism increased in older age. Moreover, age effects on materialism differed markedly between 3 core themes of materialism: acquisition centrality, possession-defined success, and acquisition as the pursuit of happiness. In particular, acquisition centrality and possession-defined success were higher at younger and older age. Independent of these age effects, older birth cohorts were oriented more toward possession-defined success, whereas younger birth cohorts were oriented more toward acquisition centrality. The economic downturn since 2008 led to a decrease in acquisition as the pursuit of happiness and in desires for personal growth, but to an increase in desires for achievement.-- (from the authors)